Diasporic Hallyu The Korean Wave in Korean Canadian Youth Culture - Yoon, Kyong; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book examines the lived experiences of diasporic Korean youth in light of the transnational flows of South Korean popular culture, known as the Korean Wave, or Hallyu. Drawing on an ethnographic study of Korean Canadian youth and their engagement with the Korean Wave, the book proposes a critical understanding of the interactions between diasporic youth audiences and popular culture. By examining the Korean Wave as diasporic cultural practices rather than the diffusion of national cultural products, the book reveals the diversified ways in which cultural flows are negotiated by audiences who take up relatively ambivalent reception positions between two or more national and cultural contexts. This book expands the scope of transnational audience studies and youth cultural studies by focusing attention on the diasporic media practices of young people. Kyong Yoon is Professor of Cultural Studies at the University of British Columbia Okanagan, Canada. He has published widely on digital media, South Korean popular culture, migration, and youth culture. He is the author of Digital Mediascapes of Transnational Korean Youth Culture (2020) and a co-author of Transnational Hallyu: The Globalization of Korean Digital and Popular Culture (2021).
1. Introduction: Thinking the Korean Wave Diasporically -- 2. Growing up Korean Canadian in the Time of the Korean Wave -- 3. Diasporic Viewing of Korean TV -- 4. K-pop Diaspora -- 5. Diasporizing Hallyu.
Keywords: Ethnology -- Asia; Culture; Popular Culture; Youth -- Social life and customs; Asian Culture; Popular Culture; Youth Culture